2016
DOI: 10.1021/acs.jmedchem.6b00571
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Alkoxyisoxazoles as Sigma-1 Receptor Antagonists with Antinociceptive Efficacy

Abstract: A novel series of sigma (σ) receptor ligands based on an alkoxyisoxazole scaffold has been designed and synthesized. Preliminary receptor binding assays identified highly potent (Ki < 1 nM) and selective σ1 ligands devoid of binding interactions with the monoamine transporters DAT, NET, and SERT. In particular, compound 53 was shown to possess significant antinociceptive activity in the mouse formalin-induced inflammation pain model when administered intraperitoneally at 40 and 80 mg/kg. Initial pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…In contrast, pre‐treatment with 16 b at 1.0 mg kg −1 s.c., followed by morphine injection (4.0 mg kg −1 s.c.), caused an increase in the opioid analgesic effect, and the MAUC value was significantly higher than that of mice receiving morphine alone (192.4 % compared with 117.3 %; # p <0.05 vs. morphine‐treated mice) (Figure b), suggesting an antagonist profile at σ 1 R. This result is of certain interest, as enhancement of the analgesic effect could decrease the necessary dose of opioid agonists in pain therapy, minimizing the adverse effects of opiate treatments . Furthermore, it has been shown that σ 1 R antagonists may have promising antinociceptive properties in different neurogenic pain models . It has also been shown that high‐affinity and selective σ 1 R antagonists dose‐dependently inhibit mechanical allodynia, which was reversed completely by the application of a selective σ 1 R agonist .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, pre‐treatment with 16 b at 1.0 mg kg −1 s.c., followed by morphine injection (4.0 mg kg −1 s.c.), caused an increase in the opioid analgesic effect, and the MAUC value was significantly higher than that of mice receiving morphine alone (192.4 % compared with 117.3 %; # p <0.05 vs. morphine‐treated mice) (Figure b), suggesting an antagonist profile at σ 1 R. This result is of certain interest, as enhancement of the analgesic effect could decrease the necessary dose of opioid agonists in pain therapy, minimizing the adverse effects of opiate treatments . Furthermore, it has been shown that σ 1 R antagonists may have promising antinociceptive properties in different neurogenic pain models . It has also been shown that high‐affinity and selective σ 1 R antagonists dose‐dependently inhibit mechanical allodynia, which was reversed completely by the application of a selective σ 1 R agonist .…”
Section: Resultsmentioning
confidence: 90%
“…[53] Furthermore, it has been shown that s 1 Rantagonists may have promisinga ntinociceptive properties in differentn eurogenic pain models. [54] It has also been shownt hat high-affinity and selective s 1 Ra ntagonists dose-dependently inhibitm echanicala llodynia, which was reversed completely by the application of as elective s 1 Ra gonist. [55] Therefore, compound 16 b deserves further investigation.…”
Section: Analgesic Activitymentioning
confidence: 95%
“…The sigma-1 receptor (σ R) is an atypical membrane protein, whose exact function remains unknown. It has been proposed that it functions as a pluripotent cell function modulator in living cells [11] that and is attracting a lot of interest due to its potential as a target against neuropathic pain [12,13,14]. While its physiological function remains elusive and the endogenous ligand is yet to be discovered, σ R is a protein target for cocaine [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…While waiting for more precise details on its physiological role, the σ 1 R is considered a pluripotent modulator able to interact with different specific proteins (e.g. binding immunoglobulin protein (BiP)) and/or components of signal transduction machineries (Su et al 2016). σ 1 R may interact with receptors for a variety of hormones/ neurotransmitters and modulate cell surface expression and/or function.…”
Section: Evidence For a Relevant Role Of σ 1 R On Cocaine Addictionmentioning
confidence: 99%
“…σ 1 R may interact with receptors for a variety of hormones/ neurotransmitters and modulate cell surface expression and/or function. Research on this protein is gaining momentum due to its potential as a target to combat neuropathic pain (Mei & Pasternak 2002, Corbera et al 2006, Sun et al 2016. Agonistic activity in the case of σ 1 R may be indirectly measured by subcellular translocation, establishment of protein-protein interactions or regulation of ion channel activity (Wu & Bowen 2008, Kim et al 2010, Su et al 2010.…”
Section: Evidence For a Relevant Role Of σ 1 R On Cocaine Addictionmentioning
confidence: 99%